The structure-function and content aspects of procrastination in employees of organization - V.V. Barabanschikova; S.A. Ivanova (Экспериментальная психология, 2018)
In this research was considered psychological structure (structure-function and content aspects) of procrastination in employees of organization as violation of conscious self-control of voluntary activity. 213 employees of the Russian industrial organization participated in the study. Based on 8 diagnostics questionnaire we constructed the model including predictors of procrastination as occupational stress syndrome, the coping strategy of avoidance and satisfaction of organization. The stability of the model was confirmed on different parts of the sample. Besides the model including content parameters changing their content depending on the selected within the sample subgroups.